2022
DOI: 10.1186/s12951-022-01498-3
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescent carbon dots (PCDs) from sour apple: a biocompatible nanomaterial for preventing UHMWPE wear-particle induced osteolysis via modulating Chemerin/ChemR23 and SIRT1 signaling pathway and its bioimaging application

Abstract: Photoluminescent nanomaterials have been widely employed in several biological applications both in vitro and in vivo. For the first time, we report a novel application of sour apple-derived photoluminescent carbon dots (PCDs) for reducing ultra-high molecular weight polyethylene (UHMWPE) wear particle-induced osteolysis using mouse calvarial model. Generally, aseptic prosthetic loosening seems to be a significant postoperative problem for artificial joints replacement, which is mainly contributed by UHMWPE-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 87 publications
1
4
0
Order By: Relevance
“…Figure 4 shows the levels of cytokines secreted from macrophages after being co-cultured with critical-sized UHMWPE-ALN wear particles in cell reactors for 1, 7, and 14 d. The secreted levels of TNF-α ( Figure 4 a) and IL-6 ( Figure 4 b) of macrophages increased with time in different groups. Particularly, the secreted levels of TNF-α and IL-6 cytokines of macrophages in the Alg + MPs + UHMWPE-ALN and Alg + MPs + UHMWPE groups were significantly higher than those in the Alg + MPs group, which demonstrated that the critical-sized wear particles would stimulate the secretion of cytokines from macrophages, which was analogous to the findings of Li et al [ 21 ]. However, the secreted levels of TNF-α and IL-6 cytokines from macrophages in the Alg + MPs + UHMWPE-ALN group were significantly lower than those in the Alg + MPs + UHMWPE group.…”
Section: Resultssupporting
confidence: 86%
“…Figure 4 shows the levels of cytokines secreted from macrophages after being co-cultured with critical-sized UHMWPE-ALN wear particles in cell reactors for 1, 7, and 14 d. The secreted levels of TNF-α ( Figure 4 a) and IL-6 ( Figure 4 b) of macrophages increased with time in different groups. Particularly, the secreted levels of TNF-α and IL-6 cytokines of macrophages in the Alg + MPs + UHMWPE-ALN and Alg + MPs + UHMWPE groups were significantly higher than those in the Alg + MPs group, which demonstrated that the critical-sized wear particles would stimulate the secretion of cytokines from macrophages, which was analogous to the findings of Li et al [ 21 ]. However, the secreted levels of TNF-α and IL-6 cytokines from macrophages in the Alg + MPs + UHMWPE-ALN group were significantly lower than those in the Alg + MPs + UHMWPE group.…”
Section: Resultssupporting
confidence: 86%
“…Photoluminescent carbon dots (PCDs) from sour apples cured a mouse calvarial osteolysis model induced by ultra-high molecular weight polyethylene (UHMWPE) wear particles. PCDs reduced UHMWPE-induced ROS stress and pro-inflammatory cytokine production to inhibit osteoclastogenesis and bone resorption in vitro [ 188 ].…”
Section: Ros-scavenging Nanotechnology In Prevention and Treatment Of...mentioning
confidence: 99%
“…Under the same settings, NF-κB can be activated by RANKL or LPS to augment particles-induced bone loss via the enhancement of osteoclastogenesis ( 206 , 207 ). Upstream stimuli-triggered NF-κB signaling could act on transcription factors (c-fos and NFATc1) and regulate the expression of osteoclastogenesis-related genes, thus promoting OC differentiation and functions ( 206 , 208 , 209 ).…”
Section: Regulatory Mechanisms Of Macrophages In Almentioning
confidence: 99%